The components of civil service in Kazakhstan. (Journal of Economic Research & Business Administration, 2015)
The article deals with topical issues of the components of the new model of civil service in Kazakhstan , the definition of public service , the differences between political andadministrative civil servants , the essence of the conceptmeritocracy , and the terms of the principle of meritocracy in the selection of staff.
Keywords: government officials; the principle of meritocracy